Two‐Terminal Direct Wafer‐Bonded GaInP/AlGaAs//Si Triple‐Junction Solar Cell with AM1.5g Efficiency of 34.1%. Issue 9 (8th July 2020) - Lackner, David; Höhn, Oliver; Müller, Ralph; Beutel, Paul; Schygulla, Patrick; Hauser, Hubert; Predan, Felix; Siefer, Gerald; Schachtner, Michael; Schön, Jonas; Benick, Jan; Hermle, Martin; et al.
Abstract : The terrestrial photovoltaic market is dominated by single‐junction silicon solar cell technology. However, there is a fundamental efficiency limit at 29.4%. This is overcome by multijunction devices. Recently, a GaInP/GaAs//Si wafer‐bonded triple‐junction two‐terminal device is presented with a 33.3% (AM1.5g) efficiency. Herein, it is analyzed how this device is improved to reach a conversion efficiency of 34.1%. By improving the current matching, an efficiency of 35% (two terminals, AM1.5g) is expected. Abstract : The terrestrial photovoltaic market is dominated by single‐junction silicon solar cell technology. However, there is a fundamental efficiency limit at 29.4%. This is overcome by multijunction devices. Recently, a GaInP/GaAs//Si wafer‐bonded triple‐junction two‐terminal device is presented with a 33.3% (AM1.5g) efficiency. Herein, it is analyzed how this device is improved to reach a conversion efficiency of 34.1%.